ESG and sustainable finance: Navigating networks, examining hypocrisy, and promoting prosociality - Sherman, Zachary (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2026)
To address the rising tensions between ESG reporting aspirations and practice, marked by hypocrisy and unfair opportunism, this thesis examines the networks and notion of Environmental, Social, and Governance (ESG) in the global finance industry. ESG literature in finance largely relies on quantitative analyses of performance metrics but new inspiration is drawn from qualitative traditions in accounting, such as sustainability accounting and social and environmental accounting, to better understand the tensions of ESG as practised. Actor-Network Theory (ANT) serves as a method theory to inform key steps in conducting the research and following both human and non-human actors in the industry. The prosocial paradigm is employed to provide a framework to distinguish exploitative gaming behaviours from cooperative actions and apply its adapted core design principles for collectives to ESG as practised. This research differs from quantitative finance studies that largely highlight market performance, motivated by the gap between ESG reporting aspirations and ESG as practised. It adopts an interpretive qualitative design, using semi-structured interviews with ESG stakeholders and document analysis, to investigate network structures, discourses, gaming patterns, and prosocial responses. Findings map the key actors in the ESG networks and portray the notion of ESG as three contested black boxes. A dominant ‘Specified ESG’ focuses on ratings and reporting and prevails among seasoned professionals and academics. In contrast, a competing ‘Broad ESG’ equates the concept with broader sustainability efforts and is prevalent among students. An emerging hybrid perspective also appears. The analysis further identifies distinct instances of both gaming behaviours and prosocial behaviours associated with ESG as practised. The thesis contributes an interpretive perspective to finance literature and illustrates the potential for prosocial sustainability reforms.